Use of three-dimensional electroanatomic mapping for epicardial access: needle tracking, electrographic characteristics, and clinical application - Yu, Ronghui; Liu, Nian; You, Binquan; Wang, Haixiong; Ruan, Yanfei; Wen, Songnan; Weiss, Peter J; Zawaneh, Michael; Su, Wilber; Tung, Roderick; Zhao, Xin; Wang, Wei; et al. (Europace (London, England), 2024)
Abstract Aims Pericardiocentesis is usually completed under fluoroscopy. The electroanatomic mapping (EAM) system allows visualizing puncture needle tip (NT) while displaying the electrogram recorded from NT, making it possible to obtain epicardial access (EA) independent of fluoroscopy. This study was designed to establish and validate a technique by which EA is obtained under guidance of three-dimensional (3D) EAM combined with NT electrogram. Methods and results 3D shell of the heart was generated, and the NT was made trackable in the EAM system. Unipolar NT electrogram was continuously monitored. Penetration into pericardial sac was determined by an increase in NT potential amplitude and an injury current. A long guidewire of which the tip was also visible in the EAM system was advanced to confirm EA. Epicardial access was successfully obtained without complication in 13 pigs and 22 patients. In the animals, NT potential amplitude was 3.2 ± 1.0 mV when it was located in mediastinum, 5.2 ± 1.6 mV when in contact with fibrous pericardium, and 9.8 ± 2.8 mV after penetrating into pericardial sac (all P ≤ 0.001). In human subjects, it measured 1.54 ± 0.40 mV, 3.61 ± 1.08 mV, and 7.15 ± 2.88 mV, respectively (all P < 0.001). Fluoroscopy time decreased in every 4–5 cases (64 ± 15, 23 ± 17, and 0 s for animals 1–4, 5–8, 9–13, respectively, P = 0.01; 44 ± 23, 31 ± 18, 4±7 s for patients 1–7, 8–14, 15–22, respectively, P < 0.001). In five pigs and seven patients, EA was obtained without X-ray exposure. Conclusion By tracking NT in the 3D EAM system and continuously monitoring the NT electrogram, it is feasible and safe to obtain EA with minimum or no fluoroscopic guidance. Graphical Abstract Graphical Abstract Demonstration of connection of pericardiocentesis needle to the EAM system and recording of needle tip electrogram. (A–C) The proximal end of a modified Tuohy needle was connected to the EAM system via a jumper wire (J), the body of needle was covered by outer sheath (N + S) except for the tip that remained electrically conductive. The needle was inserted underneath the subxiphoid at an angle of 45–60° to the body surface and was kept at a direction towards to the front one-half of the inferior wall of the right ventricle. (D) A closer view at LAO 45° of the needle tip (NT) and its relative location to the heart. The red circles represented the needle tip location when it was in the mediastinum over the diaphragm (MD), in contact with fibrotic epicardium (FP), and penetrated into pericardial sac (PS). The typical needle tip unipolar electrogram (N1) at these three locations were shown in panel F. (E) In the EAM system, the needle was detected as a bipolar catheter (yellow arrow). It was real-timely tracked and displayed with pre-acquired 3D shells of LV and RV in different projections (left: AP view; right: LAO 45° view). (F) The dominant component of the needle electrogram was the electrical activity from ventricles, namely Ned potential, corresponding to the QRS complex on surface ECG. Lower row—small Ned potential when NT in the mediastinal; middle row—larger Ned potential with small injury current (white arrow) when NT in contact with fibrotic pericardium. A PVC (blue arrow) indicated that the needle tip has been in contact with the heart; upper row—giant Ned potential with significant injury current (red arrow) when NT penetrated into pericardial sac. FP, fibrous pericardium; MD, mediastinum; PS, pericardial space; Myo, myocardium; Ned, the dominant potential on needle electrogram; J, jumper wire; N + S, needle with outer sheath; other abbreviations as Figures 1–6.